2008
DOI: 10.1128/jvi.00485-08
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Nef Induces Programmed Death 1 Expression through a p38 Mitogen-Activated Protein Kinase-Dependent Mechanism

Abstract: Chronic viral infection is characterized by the functional impairment of virus-specific T-cell responses.Recent evidence has suggested that the inhibitory receptor programmed death 1 (PD-1) is specifically upregulated on antigen-specific T cells during various chronic viral infections. Indeed, it has been reported that human immunodeficiency virus (HIV)-specific T cells express elevated levels of PD-1 and that this expression correlates with the viral load and inversely with CD4 ؉ T-cell counts. More important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 33 publications
0
64
1
Order By: Relevance
“…Elevated Tim-3 levels on T cells could potentially negatively impact the immune system's response toward all pathogens. Indeed, another exhaustion marker, PD-1, which exhibits characteristics on T cells similar to those that express Tim-3 in the acute and chronic phases of HIV-1 infection (3, 26-28) was reported to be upregulated by the HIV-1 protein Nef (16). Thus, we determined the effect of in vitro HIV-1 infection on CD4 + T cells' PD-1 or Tim-3 expression up to 72 h postinfection (Fig.…”
Section: Hiv-1 Does Not Directly Induce Tim-3 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated Tim-3 levels on T cells could potentially negatively impact the immune system's response toward all pathogens. Indeed, another exhaustion marker, PD-1, which exhibits characteristics on T cells similar to those that express Tim-3 in the acute and chronic phases of HIV-1 infection (3, 26-28) was reported to be upregulated by the HIV-1 protein Nef (16). Thus, we determined the effect of in vitro HIV-1 infection on CD4 + T cells' PD-1 or Tim-3 expression up to 72 h postinfection (Fig.…”
Section: Hiv-1 Does Not Directly Induce Tim-3 Expressionmentioning
confidence: 99%
“…To elucidate the pathway behind Tim-3 upregulation in chronic HIV-1 infection, we first postulated that a viral gene product could be driving Tim-3 expression. Indeed, HIV-1 protein Nef was shown to directly induce the expression of another exhaustion marker, PD-1, on the surface of HIV-1-infected CD4 + T cells (16). We hypothesized that viral factors, such as HIV-1 gp120, found in the serum of infected individuals, could upregulate Tim-3 by binding to certain receptors on the surface of T cells, such as the CD4 receptor, or that soluble HIV-1 Tat diffusing into T cells to drive HIV-1 replication could also be indirectly responsible (17).…”
mentioning
confidence: 99%
“…One recent study showed Nef to be associated with HIV viral antigens to specifically increase PD-1 expression through a p38 MAPK-dependent mechanism. 41 HBcAg is the major component encoded by HBV DNA, so we focused on the correlation between HBcAg and PD-1 upregulation. In the study on lymphoma, 56 PD-L1 expression was shown to be dependent on the ERK and p38 MAPK signaling pathways.…”
Section: Pd-1 Upregulation By Hbcag In Hbv Infectionmentioning
confidence: 99%
“…It has been reported that Nef induces PD-1 transcription, while specific inhibitor against p38/MAPK inhibits Nef activity and effectively blocks PD-1 upregulation. This suggests that Nef-mediated PD-1 expression is dependent on p38/MAPK activation [19]. In HBV infected patients, PD-1 expression is increased on CD4 + T cells from peripheral blood compared to those in healthy volunteers.…”
Section: Function and Expression Of Pd-1mentioning
confidence: 97%